Then a miracle occurs focusing on behavior in social psychological theory and research : Purdue Symposium on Psychological Sciences - Purdue Symposium on Psychological Sciences 2008 : Purdue University); Agnew, Christopher Rolfe (New York ; Oxford : Oxford University Press, 2009)
Chapters in this volume review key issues in the study of social psychology, with contributions from some of the world's leading social and personality psychologists.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Interbehavioral psychology -- Congresses; Social psychology -- Congresses